Analisis Rasio Keuangan terhadap Profitabilitas pada Perbankan Indonesia - Heri Susanto; Nur Kholis (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2016)
This research aims to analyze the influence of financial ratio to measure the level of profitability with proxy in ROA well partially or simultan. Financial ratio include CAR, CR, LDR, BOPO and NPL, NIM. This research is using purposive sampling technique to collect data population from financial reports Bank-State Owned 2007-2014. The analysis of data used descriptive statistics, classic assumption test, multiple regression analysis, hypothesis testing and analysis of the coefficient of determination (R2). The results of this research showed that as partially variable CAR, NPL and NIM has significant influence to the ROA, and variable CR, LDR and BOPO doesn’t have influence to ROA, and variable NIM have dominant influence to the ROA. While simultaneously variable CAR, CR, NPL, NIM, LDR and BOPO has significant influence on ROA. Based on the results of value 81,1% of coefficient of determination (R2), all independent variables have strong influence in explaining the dependent variable.